Pengaruh Guna Lahan Terhadap Penurunan Infiltrasi di Kota Batu - Permanasari, Puspa; Bisri, M.; Suharyanto, Agus (Fakultas Teknik, Universitas Brawijaya, 2012)
This study aimed to evaluate the condition of existing land use in years 2010 with the Spatial Plan Batu years 2003 to 2013 to determine the effect of land use on infiltration in Batu City. The method used in this study is regression analysis and Analysis Hierarky Proces. The results showed there is a dominant influence of land use on infiltration and analysts have a different outcome each district. Existing land use conditions in 2010 have an influence on the decline in power of absorbing rainwater into the soil. It can be seen from the declining value of the infiltration in Batu declined 34.915.235 mÂ³ / year or 13% of land use in 2003. To ensure the conservation of water resources in terms of preventing the destructive force of water, the ground water reserves in 3 (three) districts in the town of Batu need to consider land use contained in the spatial plan that no longer have the conversion of land to land up which can lead to reduced capacity and water potential capacity.Keywords: conservation, land use, infiltration.